Stevia rebaudiana Bertoni Leaves Extract as a Nutraceutical with Hypoglycemic Activity in Diabetic Rats - Keri Lestari; Abdurahman Ridho; Nuning Nurcayani; Zelika Mega Ramadhania; Melisa Intan Barliana (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: The prevalence of diabetes mellitus is growing every year, including in Indonesia. Medicinal herbs were used empirically for lowering blood glucose. One of potential herb to have hypoglycemic activity is Stevia. Stevia rebaudiana Bertoni leaves contain stevoside, a natural, low-calorie sweetener that is 300 times sweeter than saccharose. In this study, we aimed to explore the hypoglycemic activity of S. rebaudiana Bertoni leaves extract in a rat model of type 2 diabetes mellitus (T2DM). METHODS: Male Wistar rats were feed high-fat, high-carbohydrate feed and sugar solution for 74 days to induce a diabetic rat model. The animals were then divided into five groups consisting of a negative control group treated with 2% Pulvis Gom Arabicum; a positive control group treated with Metformin 45 mg/kg body weight (BW); and three test groups treated with aqueous extract of S. rebaudiana Bertoni leaves at doses of 3.125, 6.25 and 12.5 mg/kg BW for 36 days. Blood glucose was measured on days 14, 28 and 36.RESULTS: The results showed that blood glucose levels over 36 days were significantly (p=0.043) lower in the group treated with S. rebaudiana Bertoni leaves extract. Further Newman-Keuls analysis suggested that the hypoglycemic activity of S. rebaudiana Bertoni leaves extract was dose-dependent. CONCLUSION: Our results indicate that S. rebaudiana Bertoni leaves extract has a potential role as a hypoglycemic agent in the treatment of T2DM.KEYWORDS: Stevia rebaudiana Bertoni, nutraceuticals, hypoglycemic, diabetic rats